2014
DOI: 10.1245/s10434-014-4181-9
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Hepatic Steatosis on Disease-Free Survival in Patients with Non-B Non-C Hepatocellular Carcinoma Undergoing Hepatic Resection

Abstract: The prognosis of NBNC HCC was similar to that of BC HCC. Among NBNC HCC patients, NAFLD-associated HCC patients had a relatively low recurrence risk. Absence of steatosis in hepatic parenchyma had a significant impact on disease-free survival in NBNC HCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
(29 reference statements)
4
9
1
Order By: Relevance
“…Furthermore, AFP levels >1000 ng/mL, preoperative tumor rupture, local extrahepatic disease, poor tumor differentiation, cirrhosis, and steatosis did not significantly distinguish short-term from long-term survivors. These findings were consistent with some, but not all, prior studies 8,1927 . This is likely due to the heterogeneity of HCC patients and thus it is difficult to identify prognostic factors that are widely applicable.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, AFP levels >1000 ng/mL, preoperative tumor rupture, local extrahepatic disease, poor tumor differentiation, cirrhosis, and steatosis did not significantly distinguish short-term from long-term survivors. These findings were consistent with some, but not all, prior studies 8,1927 . This is likely due to the heterogeneity of HCC patients and thus it is difficult to identify prognostic factors that are widely applicable.…”
Section: Discussionsupporting
confidence: 93%
“…The effects of tumor diameter, multiple tumor nodes, and vascular invasion, which are relevant to aggressive behavior of a tumor, on the prognosis of HCC have been reported in many previous literatures. 6,9,[22][23][24][25] In addition, several studies demonstrated the unfavorable effect of these factors in NBNC-HCC, 9,22 which is consistent with our results. GGT, a cost-effective and easily accessible serum biomarker, has been reported to have diagnostic and prognostic effects in various malignancies.…”
Section: Discussionsupporting
confidence: 92%
“…Although we found that MVI does not influence patient outcome after LDLT [ 1 ], 77.8% of patients with HCC recurrence presented with distant metastasis, of which 66.7% were associated with MVI in the explanted liver ( Table 1 ). Given that circulation biomarkers have been previously identified from peripheral blood, it is likely that MVI influences recurrence after LDLT [ 25 26 ]. A recent study showed that higher VEGF plasma levels before liver transplantation may influence HCC recurrence [ 27 ].…”
Section: Discussionmentioning
confidence: 99%